Sjögren’s syndrome-associated microRNAs in CD14(+) monocytes unveils targeted TGFβ signaling - Williams, Adrienne E. G. (Arthritis Res Ther, 2016)
BACKGROUND: Sjögren’s syndrome (SjS) monocytes have a pro-inflammatory phenotype, which may influence SjS pathogenesis. MicroRNAs (miRNAs) are small endogenously expressed molecules that can inhibit protein expression of their targeted genes and have important functions in regulating cell signaling responses. We profiled miRNAs in SjS monocytes to identify a SjS-specific miRNA profile and determine the potential roles of miRNAs in SjS pathogenesis. METHODS: Total RNA was extracted from healthy control (HC, n = 10), SjS (n = 18), systemic lupus erythematosus (SLE, n = 10), and rheumatoid arthritis (RA, n = 10) peripheral blood CD14(+) monocytes for miRNA microarray analysis. To validate select miRNAs from the microarray analysis, the original cohort and a new cohort of monocyte RNA samples from HC (n = 9), SjS (n = 12), SLE (n = 8), and RA (n = 9) patients were evaluated by quantitative reverse transcription (RT)-PCR. Functional predictions of differentially expressed miRNAs were determined through miRNA target prediction database analyses. Statistical analyses performed included one-way analysis of variance with Bonferroni post tests, linear regression, and receiver operating characteristic curve analyses. RESULTS: MiRNAs were predominantly upregulated in SjS monocytes in comparison with controls. Quantitative RT-PCR confirmations supported co-regulation of miR-34b-3p, miR-4701-5p, miR-609, miR-300, miR-3162-3p, and miR-877-3p in SjS monocytes (13/30, 43.3 %) in comparison with SLE (1/17, 5.8 %) and RA (1/18, 5.6 %). MiRNA-target pathway predictions identified SjS-associated miRNAs appear to preferentially target the canonical TGFβ signaling pathway as opposed to pro-inflammatory interleukin-12 and Toll-like receptor/NFkB pathways. CONCLUSIONS: Our results underscore a novel underlying molecular mechanism where SjS-associated miRNAs may collectively suppress TGFβ signaling as opposed to pro-inflammatory interleukin-12 and Toll-like receptor/NFκB pathways in SjS pathogenesis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13075-016-0987-0) contains supplementary material, which is available to authorized users.